METAL COMPLEXES OF CURCUMIN AND DMB LIGAND , GEOMETRICAL AND BIOLOGICAL - Ali, Fatima; Hasann , Hasann (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2026)
This study was aimed to investigate synthesis and characterization of two ligands type (azo-linked Schiff-base) with its complexes. Precursor (W) obtained by reaction of diazonium salt of 1-Naphthyl amine with O-tolidin in water as a solvent via 2:1 mole ratio. Azo-linked Schiff-base ligands synthesized via the reaction of 3, 3'- dimethyl-5,5'-bis((E)-pyridin-3-yldiazenyl)-[1,1'-biphenyl]-4,4'-diamine with curcumun or dibenziyl methan for obtaining 4, 4', 4'', 4'''- ((1E, 1'E, 6E, 6'E) - ( (3, 3'- dimethyl-5, 5'-bis((E)-pyridin-3-yldiazenyl)-[1,1'-biphenyl]-4,4'-diyl) bis (azaneylylidene)) bis(5-hydroxyhepta-1,6-diene-1,7-diyl-3-ylidene))tetrakis(2-methoxyphenol) (H2L1) or 3,3'-((3,3'-dimethyl-5,5'-bis((E)-naphthalen-1-yldiazenyl)-[1,1'-biphenyl]-4,4'-diyl)bis(azaneylylidene))bis(1,3-diphenylpropan-1-ol) (H2L2). Complexes synthesis achieved via reaction of the metal ion salts CoII, MnII, CuII, NiII and CdII with azo-linked Schiff-base ligands within (2-1) mole ratio. Characterization of prepared ligands and complexes through spectroscopic and analytical techniques included; conductance, microanalysis, thermal analysis and magnetic susceptibility (for complexes) measurements along with NMR, UV-Vis and FTIR spectroscopies